THE REPRESENTATION OF UNAS STUDENTS AND POLICE OFFICERS IN THE JAKARTA POST DURING THE 2008 FUEL PRICE INCREASE(A CRITICAL DISCOURSE ANALYSIS) - Meity Prihartanti, - (2008)
This study which is entitled "The Representation of UNAS Students and Police Officers in the Jakarta Post During the 2008 Fuel Price Increase" was conducted to investigate two articles concerning the issue of the increase of the fuel price which were published in the Jakarta Post during May, 27th 2008 until July, 2th 2008. The study investigates three problems, i.e. the representation of UNAS students, the representation of police officers, and the ideologies behind the representations. The data analysis was conducted by employing a Critical Discourse Analysis (CDA) framework. In addition, Systemic Functional Grammar (SFG) was used as the tool of analysis. It comprises the analysis of thematization, transitivity, nominalization, and passivization. The results show that the Jakarta Post tended to represent the police officers negatively. Based on the transitivity, the police officers were largely represented as the causal agent being responsible for the death of a UNAS student (Maftuh) (35.93%). It was also supported by the use of the nominalization (3.57%) and passivization (8.92%). On the contrary, UNAS students were depicted positively (44.44%). The students tended to be represented as independent, active and powerful. In general, the students were represented as heroes for underprivileged society. In this case, the students were heavily topicalized (38.70%) by the Jakarta Post compared to the police officers. It means that the Jakarta Post appeared to side with one party, namely, UNAS students. In addition, the students were depicted as a victim of the government's policy and police officers' brutal action (26.66%). This elaboration implied that the Jakarta Post tended to try to highlight the role of the students over the case. It also indicates that the Jakarta Post tried to get readers' sympathy. Accordingly, such representations signify that the Jakarta Post has depicted the actors of the case unfairly.